Gambaran Pengetahuan Perawat Tentang Perawatan Luka Modern Dressing di Satu Rumah Sakit Swasta di Indonesia Barat - Anggiriani Meilin Br. Sidabutar; Rika Anggelina Patty; Sonta Simanjuntak; Lia Kartika; Sumiaty Aiba (Poltekkes Kemenkes Bengkulu, 2019)
Currently, the wound care technique is experiencing rapid development, especially modern wound dressing treatments that maintain the moist dressing principle. Wound care is one of the nurses' skills that should be known by all nurses. Data shows that five out of eight nurses are not aware of modern wound dressing techniques. This condition was becoming a cause for concern because inadequate knowledge can make a non-comprehensive wound assessment and treatment that can slow down or even hinder the client's wound healing process. This study aimed to determine the description of nurses' knowledge of modern dressing wound care. Quantitative descriptive methods with total sampling techniques were conducted on 50 respondents who worked in the inpatient rooms on 5th, 6th, and 7th floor in June-July 2019. Univariate analysis was used to obtain an overview of nurses' knowledge of modern dressing wound care techniques. Most of the nurses' knowledge about modern wound dressing care has sufficient knowledge, namely 33 people (66%). Special training and seminars on modern dressing need to be carried out to increase knowledge and ensure the authority of nurses in wound care. Further researchers are advised to identify factors that influence nurses' knowledge of modern dressing wound care.